Impact Analysis of Job Design, Leadership Styles, Employee Expectation and Employee Motivation to Employee Performance (Study on IT Operations Organization at PT. Indosat Tbk) - Gunarto, Gunarto; Rudito, Bambang; Bangun, Yuni Ros (The Indonesian Journal of Business Administration, 2012)
The study aims to investigate and identify factors those make IT Operation employees at PT. Indosat Tbk motivated while doing their job, and their impact to employee's performance. This writing talk about relationship between, job design, and employee's expectation, leadership styles and motivational level of employees to employee's performance. this writing based on study that conducted in 2011 at IT Operations Organization at PT Indosat Tbk. This writing comes up in response on intensive telecommunication industry competition in Indonesia, the low performance of Indosat compared with the other competitor in last 3 years, and the major roles of IT Operations in daily operation of Indosat. Â In Indosat, IT Operations has responsible to deliver services to customer, keep & maintain the services and products, implement new product in system, second layer in handling complaints, provide accurate data for the other group. The critical part of IT Operations is responsible for maintaining Indosat Revenue Generator (Single Electronics Voucher, Integrated Voucher Database that equal for 40 billion rupiah per day) daily operations, which provide the customers ability to recharge/top up money to their number in 24x7 operation time. Keywords: Job design, Leadership styles, expectation, motivation, performance, telecommunication, Information Technology